Proverbs 1-9. historical commentary on the old testament, James Alfred Loader : book review - Keefer, Arthur (Old Testament essays, 2015)
James Alfred Loader, associated with the Universities of Vienna and Pretoria, has contributed a substantial volume to the study of Prov 1 - 9. He has previously written on other areas of the OT, most notably Ecclesiastes. As a part of the Historical Commentary on the Old Testament series, the Proverbs commentary incorporates the reception history of the biblical text. For Proverbs, this limits mainly to medieval and post-medieval Rabbinic literature, along with Christian interpreters of the patristic and Reformation periods. In a 46 page introduction, Loader briefly addresses issues of date, structure, provenance, versions, and a summary of the message and theology of Proverbs. The bulk of the introduction includes four thematic essays on the social setting of wisdom, plus the concepts of order, revelation, and retribution.